Structure and Function of the Urokinase Receptor - Mondino, Anna; Resnati, Massimo; Blasi, Francesco (Thrombosis and Haemostasis, 1999)
The binding of the urokinase plasminogen activator (uPA) to its receptor (uPAR) regulates cell adhesion, surface proteolysis, chemotaxis and cell extravasation in a number of experimental systems. Recent evidences have suggested that uPAR can by itself mediate chemotaxis of human monocytes and cause profound changes in cytoskeletal organization indicating that this receptor has the properties of a cell-surface regulated chemokine. Indeed, it is likely that upon binding to uPA, uPAR undergoes a conformational change that uncovers a new epitope located in the linker region between domain 1 and 2 of the receptor and is endowed with a potent chemotactic activity. This conformational change can be mimicked in vitro by enzymatic processing of a recombinant receptor. We have shown that chymotrypsin cleaves uPAR between domain 1 and 2 in an area that can be also cleaved by uPA at high efficiency and generate a receptor that can mediate monocytes migration independently of uPA binding. This mechanism is pertussis-toxin sensitive and involves activation of tyrosine kinases and cytoskeletal reorganization events in vitro. These studies indicate that in addition to its receptor function, upon binding to uPA, uPAR becomes a pleiotropic ligand for other still to be identified surface molecules.
Keywords: Urokinase receptor; chemotaxis; cytoskeleton; tyrosine kinases; G-proteins